Law Enforcement Against Criminal Acts Participates In Continuous Money Laundering As A Continued Act (Study of Supreme Court Decision Number: 559 Pk/Pid.Sus/2022) - Isa Ramiati; Rahul Ardian Fikri; Abdul Razak Nasution (International Journal of Society and Law, 2024)
Money laundering is a serious crime that threatens the economic and social systems, often involving sophisticated methods and multiple parties. This study analyzes the application of law in the Supreme Court decision Number: 559 PK/Pid.Sus/2022, which addresses the crime of continuous money laundering involving participation. The defendant, Gulabray Naraindas Keswani, was found guilty of continuous money laundering and sentenced to prison and a fine. Through an analysis of the legal considerations and application of legal principles such as inclusion (deelneming) and continuing acts (voortgezette handeling), this study highlights the judiciary's commitment to eradicating money laundering and its implications for law enforcement. This case sets a significant precedent for combating similar crimes in Indonesia.